Large-scale sediment modeling with inertial flow routing: Assessment of Madeira river basin. (March 2022) - Föeger, Lizandra Broseghini; Buarque, Diogo Costa; Pontes, Paulo Rógenes Monteiro; Fagundes, Hugo de Oliveira; Fan, Fernando Mainardi
Abstract: The flow routing module in several large-scale erosion and sediment transport models generally adopts simplifications that ignore important physical aspects of river dynamics. In this study we compare for the first time the results generated by a large-scale erosion and sediment transport model, using two different flow routing approaches: a combined Saint-Venant and Muskingum-Cunge method and the Inertial flow routing. For this assessment, simulations are performed with the MGB-SED model. We evaluate sediment characteristics such as suspended sediment load and concentration, floodplain effects, and the flux of suspended sediment within the Madeira River basin. The simulation with the inertial approach presents satisfactory results, similar to those achieved with the combined Saint-Venant approach for lowland rivers and the Muskingum-Cunge method for steeper rivers. Also, Inertial module is capable to represent the complex processes of the basin, but with easier preprocessing and numerical features, thus promising expanded capabilities for large-scale simulations. Highlights: Evaluation of the relative weights of the Saint-Venant equation terms. Large-scale sediment model using inertial flow routing method. The average percentage that is represented by the advective inertial term is 0.15%. Similar results were achieved with full Saint-Venant equations for lowland rivers.